Association of SDF-1 and its receptor CXCR4 polymorphisms on the susceptibility of diabetic retinopathy in the Taiwanese population - Peng, Shu-Yen; Chuang, Chih-Chun; Hwang, Yih-Shiou; Yen, Chieh-Hung; Lee, Chia-Yi; Yang, Shun-Fa (Frontiers in Genetics, 2023)
Stromal cell-derived factor-1 (SDF-1) and its receptor CXC chemokine 4 (CXCR4) have been demonstrated to play critical roles in diabetic retinopathy (DR). This study investigated if single-nucleotide polymorphisms (SNPs) of the SDF-1 and its receptor CXCR4 are correlated with diabetic retinopathy (DR). Three SDF-1 SNPs including rs1801157 (G/A), rs2297630 (G/A), rs266085 (T/C) and two CXCR4 SNPs including rs2228014 (C/T) and rs6430612 (C/T) were chosen and genotyped via the TaqMan allelic discrimination for 454 non-DR subjects and 276 DR individuals. Our results revealed that subjects carrying the SDF-1 SNP rs2297630 GA (AOR: 2.962, 95% CI:1.279-6.861, P=0.011) and SDF-1 SNP rs2297630 GA+AA (AOR: 3.095, 95% CI:1.394-6.872, P=0.006) had significantly higher risk for non-proliferative diabetic retinopathy (NPDR) groups than in the non-DR group. Further analyses using the datasets from the Genotype-Tissue Expression (GTEx) Portal revealed that the SDF-1 SNP rs2297630 GA and AA genotypic variants have higher SDF-1 expression than the GG wild-type alleles (P=0.000016). In conclusion, our findings revealed that the SDF-1 SNP rs2297630 was associated with NPDR.